A237 PROSTATE EXAMINATION AT TIME OF COLONOSCOPY: A SURVEY OF PATIENTS, GENERAL PRACTITIONERS (GP'S), AND ENDOSCOPISTS. (15th March 2019) - Syed, A; Borgaonkar, M
Abstract: Background: Most colonoscopies begin with a digital rectal exam. This may or may not include a digital prostate exam in male patients. Some patients believe their prostates are examined at time of colonoscopy, and hence, they believe they are also being screened for Prostate Cancer. It is unclear whether General Practitioners (GP) alter their Prostate Cancer screening practices if a patient had a recent colonoscopy. The beliefs of Endoscopists with regards to prostate examination during colonoscopy is not known. Aims: The present study was undertaken to investigate the perceptions and practices surrounding prostate exams at time of colonoscopy. Methods: 34 male patients were recruited from the gastroenterology unit at the Health Sciences center via a voluntary confidential survey. 15 General Practitioners (GP's) from various clinics in St. John's, NL were recruited via a voluntary confidential survey. 21 Endoscopists (Gastroenterologists and General Surgeons) were recruited via an electronic mailing list via an online voluntary confidential survey. Results: 44% of patients believed that the prostate was examined during colonoscopy. 87% felt that it should be examined during each colonoscopy. 93% of GP's did not reduce their frequency of prostate cancer screening when patients had a recent colonoscopy. 20% GP's expected the prostate to be examined at time of colonoscopy. 43% of Endoscopists reported performing prostate exams at least 75% of the time, and 28.5% performed them during each colonoscopy. 29% of Endoscopists believed that patients expect for their prostate to be examined during colonoscopy. 62% do not feel confident in recognizing prostate pathology on digital examination. Conclusions: The results of this survey reveal that most Endoscopists do not perform prostate exams, even though an overwhelming majority of patients believe that the prostate should be examined during colonoscopy. The majority of GP's do not alter their prostate cancer screening practices if their patients had a recent colonoscopy. This study highlights a major discrepancy that exists between patient expectation and Endoscopists' practices in regards to prostate exams during colonoscopy. Funding Agencies: None